The role of HR information system in boosting the performance of employee - Johan Hendri Prasetyo; Joko Ariawan (Institute of Computer Science (IOCS), 2023)
The massive development of information and communication technology requires companies to be able to adapt and implement the HR information system as a medium in developing work systems in companies. This research has purpose to identify and further analyze regarding the role of HR information system in improving employee performance both directly and indirectly which is through competence and work discipline. This research applied quantitative method with causality approach by taking sample of 200 respondents through snowball sampling technique. According to the research results and the analysis of data, it can be said that HR information system has capacity to increase the performance of employees at PT XL Axiata both directly and indirectly (through) competence and work discipline as mediating variables. Apart from having an influence towards the employee performance, based on these results it is also stated that HR information system could improve the competence and work discipline of employees at PT XL Axiata.